Acute Rheumatic Fever in Children: A Case Report - Rifah Zafarani Soumena (Nusantara Science and Technology Proceedings, 2023)
Acute rheumatic fever remains the most important cause of acquired heart disease in children and young adults in the world. Acute rheumatic fever it self is rarely fatal, yet up to 16 years of life and 3 years of quality-adjusted life attributable to disability are lost per case of rheumatic heart disease. For this reason, the World Heart Federation has made the elimination of acute rheumatic fever and control of rheumatic heart disease 1 of the 6 main goals in its strategic plan through 2015. We present a case study of a 12-year-old girl with a complaint of dyspneu since 4 days ago, fever for a months and joint pain involving the small joints of the hands, knees, and ankles for a months. Physical examination composmentis, blood pressure was 90/50 mmHg, heart rate 110 time/min, regular, breathing 34 times/min, temperature 38,3°C. Generalize pale, thoracic with retraction, cardiovascular examination was normal except for a grade 3 holosystolic murmur with the highest intensity at the apex, no hepatomegaly and warm extremity. Radiology examintation we found cardiomegaly. From echocardiography examination revealed severe mitral regurgitation, mild aortic regurgitation, and diffuse mild pericardial effusion. Laboratory examination complete blood count revealed hemoglobin = 10.0 g/dL, white cell count = 15,4*1000 uL, platelets = 333*1000 uL. Based on the revised Jones criteria for moderate to high-risk populations, patient had one major criteria (presence of, carditis) and two minor criteria (fever of ?38.5°C and atralgia), for which a diagnosis of acute rheumatic fever was made.